Refining behavioural analysis to promote the use of a milder model of stroke - Ahmed, Jewel (2020)
The intraluminal filament model is the most commonly used model of stroke and has been imperative to our understanding of this disease. Nonetheless, this model has several disadvantages, such as high variability and poor animal welfare. An alternative model that could be useful is the distal middle cerebral artery occlusion (dMCAO) of stroke, which produces far more reproducible lesions and better animal welfare. This model could be useful for preclinical stroke studies whilst addressing the 3R’s; the refinement, reduction and replacement of animals for scientific purposes. The caveat is that the dMCAO model is mild and primarily affects the somatosensory cortex (including the barrel cortex, primary forelimb and hindlimb areas and the secondary somatosensory cortex) whilst leaving the motor cortex mostly spared. Therefore, detection of functional deficits is difficult and because of this the dMCAO model is seldom used. The overall aim of this thesis was to develop methods to improve the detection of functional deficits in the dMCAO model.